2021
DOI: 10.20914/2310-1202-2020-4-60-68
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and practical approaches to the development of new-generation confectionery products

Abstract: A modern progressive direction in the development of confectionery production is the creation of new resource-saving technologies and the development of flour confectionery products with a reduced energy value based on the use of various types of non-traditional and local raw materials. The application of oilseed cake in the food industry makes it possible to enrich products chemical composition with proteins, lipids, dietary fiber, vitamins and minerals. The use of amaranth oil cake as a dry component allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In addition, the air layer can be used in various technological operations as a cool-heat agent, it has a high sensitivity to changes in both the mass and the area of the support surface of the recognizable product. The developed classifications of devices and products are the initial step for coding a generalized system of the type "product-working surface-pneumatic chamber" and developing a software product for the purpose of automated design of modern technological equipment with specified technological parameters and functions [2,3,10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the air layer can be used in various technological operations as a cool-heat agent, it has a high sensitivity to changes in both the mass and the area of the support surface of the recognizable product. The developed classifications of devices and products are the initial step for coding a generalized system of the type "product-working surface-pneumatic chamber" and developing a software product for the purpose of automated design of modern technological equipment with specified technological parameters and functions [2,3,10].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal stage for introducing microalgae components has been established -the additive's boiling stage and effective dosage in 2.5% concerning the sugar mass. The inclusion of microalgae in the caramel recipe increases many qualities of the finished product, including nutritional value, and the resulting product can be considered functional [37]. The inclusion of spirulina in the caramel composition does not affect the stability of the finished product to sugar during storage.…”
Section: The Use Of Spirulina In the Food Industrymentioning
confidence: 99%
“…Analysts have found that recently the share of protein consumption in Russia has decreased by 30-35% [4]. One of the main ways to eliminate protein deficiency in human nutrition is to introduce products with a high biological value into everyday diet [5]. A promising solution in this direction is the rational use of import-substituting domestic food products with universal functional and technological properties, increased nutritional and biological value.…”
Section: Formulation Of the Problemmentioning
confidence: 99%